There Are No Genuine Disagreements about Funniness - Badovinatz, Eric (Stance: an international undergraduate philosophy journal, 2015)
I argue that there are no genuine disagreements about whether something is funny. My argument rests largely on the premise that something is funny only if someone experiences it as funny. The bulk of this paper is spent supporting this premise, primarily through an analysis of the meaning of “funniness.” The rest of the paper is spent demonstrating how my conclusion follows from this premise.